Strategies for Using Facebook with Psychology Perception in The Student Recruitment to Study in Psychology Program under The COVID-19 Pandemic - Tantasawat, Dr.Vipaporn (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2022)
Employing Facebook for recruiting bachelor’s students under the situation an outbreak of coronavirus disease 2019 was one of the methods that help maintaining social distancing. At present, however, there have been no academic procedures specifically designed for such a recruitment method. It was advantage to discover a systematic student recruitment method via Facebook which can create understanding and increase confidence for those who apply for a bachelor’s degree in Counseling Psychology and Guidance program. This article discussed on the process of employing Facebook for recruiting new students and the application of psychological perceptions, including positive reinforcement theory, gestalt theory, and color psychology through Facebook for the recruitment. These can be applied to other online recruitment processes under the situation an outbreak of coronavirus disease 2019 or even under other possible crises in the future.